2006
DOI: 10.1002/nme.1853
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of substation grounding grids buried in both horizontal and vertical multilayer earth model

Abstract: SUMMARYIn the simulation of quasi-static electromagnetic fields produced by a point source located in both horizontal and vertical multilayer media, the conventional image method requires an infinite number of images to get an accurate solution, while the method of quasi-static complex images needs only a few ones. Based on the method of quasi-static complex images, the closed form of Green's function of a point source in both horizontal and vertical multilayer earth model is derived through matrix pencil (MP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 17 publications
0
43
0
Order By: Relevance
“…The goal of the proposed hybrid method [18][19][20][21] is to obtain a frequency-dependent equivalent electric circuit, as done in other fields [22][23][24][25] for the grounding system where all the inductive, capacitive and conductive couplings among different conductor elements are accounted for and their analysis can be carried out in the frequency domain.…”
Section: Grounding System Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of the proposed hybrid method [18][19][20][21] is to obtain a frequency-dependent equivalent electric circuit, as done in other fields [22][23][24][25] for the grounding system where all the inductive, capacitive and conductive couplings among different conductor elements are accounted for and their analysis can be carried out in the frequency domain.…”
Section: Grounding System Analysismentioning
confidence: 99%
“…z 0 , while the second term is smooth and can be easily evaluated with standard Gaussian quadrature formulas. When the first term in (19) is included in the source linear integral in (17), the logarithmic singularity must be accurately integrated on the linear element, and this job can be carried out by using the modified quadrature rules proposed by Wandzura in [39].…”
Section: Singular Termmentioning
confidence: 99%
“…To analyze the complex grounding system, there are a lots of published papers to attack the problem [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], among these papers, equipotential mathematic hypothesis has been used in References [4,6,8,9,12,[14][15][16][17][18]22], unequal-potential mathematic model hybrid a boundary element method (BEM) or method of moment (MoM) and conventional nodal analysis method has been adopted in References [5,7,13,[19][20][21]. Specially the BEM is used in References [6,8,9,[18][19][20][21][22], otherwise the MoM is used. Meanwhile, we found that different electromagnetic theory has been introduced to solve the problem, direct current electric field or electrostatic field theory has been used in References [4,6,…”
Section: Introductionmentioning
confidence: 99%
“…(1) and (2), we can get scalar Green's function for monopole and vector Green's function for vector dipole. For more details about the derivation process refer to [12,14,[20][21][22] for scalar Greens' function and [20][21][22] for vector Green's function. Here, we will simply give, as examples, the formula for scalar Green's function …”
Section: The Closed Form Of Scalar or Vector Green's Function Of Monomentioning
confidence: 99%
“…To better describe the grounding problem in low frequency domain (50 or 60 Hz and higher harmonic wave), in recent years the quasistatic electric field theory has been utilized to combine with the equal potential model [10][11][12][13][14] and unequal potential model [9,[15][16][17][18][19][20][21][22]. In these models, only the propagation effect of electromagnetic wave is ignored.…”
Section: Introductionmentioning
confidence: 99%